Islami In Indonesia: An Introductory Remarks - M Machasin (Al-Jami'ah Research Centre, 1992)
To speak about Islam in such a big population will involve a very large range of problems, from the insufficiency of the materials, to the disputes over subjects on which several researches have been done. The most important historicals are those related to its coming in this archipelago. To this day, no one can tell exactly when it came here for the first time, why it was accepted by the majority of the people, who propagated it here etc. The social scientist faces the problem that Islam is expressed here, as in any other part of Muslim world, in a vast number of variations. We can see, on the one hand, many